Re-Utilization of Banana Waste into Compost - Sophia Shanti Meilani; Noveria Eka Susyani (Universitas Darussalam Gontor, 2021)
Organicwaste frequently becomes problem in every city in Indonesia because the quantity keeps increasing whiledisposal area is very limited.Most of organic waste is transported to final disposal area despite its potential to be converted into compost. This is also the case in Bekasi City. Banana stem wasteis organic waste from agricultural sector, which creates problemsbecause ofits weightand volume. Composting is an alternative to treat this type of organic waste. Banana stem contains Carbon, Nitrogen, Fosfor, Kalium which are important materials for compost . This study wasconducted to identify the potential of converting banana stem waste into compost. Composting of banana stem wasset to 25 days. During composting process temperature increasedup to 45oC. The increase of temperature indicated microorganism activity in decomposing banana stem waste. Final result of composting revealedthat banana stem compost contains C-Organic, Phosphorous and moisture content that comply with the requirement of compost according to SNI 19-7030-2004. Banana stem compost also contain Kalium and Mangan but the concentration were lower than the standard. Composting of banana stem gavemany benefits. It reducedorganic waste quantity and the product can be reused as fertilizer. Banana waste compost providednutrients that are required for crops productivity